Effectiveness and safety of the combination drug "Femo-Klim" evaluated in patients with former cancer and moderate menopausal disorders - О. Р. Vinogradova; О. А. Biryuchkova; S. V. Mikheeva (IRBIS LLC, 2024)
Aim: to assess effectiveness and safety of a combination phytoestrogen-based product "Femo-Klim" in treatment of moderate climacteric disorders in gynecological cancer patients.